ANALISIS PUTUSAN PENGADILAN NEGERI PADANGSIDIMPUAN NOMOR, 473/PID.B/2008/PN.PSP TENTANG TURUT SERTA DALAM MELAKUKAN TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN - Indra Purba Harahap; Sutan Siregar (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Research on the verdict issued or handed down by the Judge of Padangsidimpuan District Court against the perpetrator with the title of the study then the formulation of this research problem is, how does the Judge impose the penalty on the perpetrator of the crime participating in the theft by ballast according to the Verdict of padangsidimpuan District Court Number, 473/Pid.B/2008/PN.Psp?  and what is the dominant factor why a person wants to participate in helping to commit a crime of theft by ballast in the District Court area of Padangsidimpuan?  The research method that the authors used in the writing of this study is descriptive research and normative research which is the study that is done with the results of the author's interview with the respondent and also conducts research on the data and files related to this research and also through a ruling of the Padangsidimpuan District Court Number, 473/Pid.B/2008/PN.Psp which has legal force fixed by doing Field Research and Field Research. The judge sentenced the perpetrator of the crime of participating in the theft by ballast according to the District Court's Verdict padangsidimpuan Number, 473/Pid.B/2008/PN.Psp where the sentence was handed down and based on Article 363 paragraph (1) to 3, 4 and 5 with a sentence of one year and cut with during the period of detention both against the person who participated in committing the crime of theft with a ballast and that is the dominant factor because a person wants to do the role of helping to commit a crime of theft in the jurisdiction of padangsidimpuan District Court is due to the fact that poverty expects rewards and the resentment